An evolving synthetic biological platform for alkane production - Kennerley, J (2022)
Fossil fuels are finite and polluting, but underpin almost every system and product we use in the modern world. Anthropogenic greenhouse gas emissions from fossil fuel combustion are the major driver of climate change, yet demand for these fuels continues to grow. Alleviating global reliance on fossil carbon, especially in the transport sector, demands a drop-in compatible substitute with comparable energy density and fuel chemistry to diesel, jet fuel, or gasoline. If derived from atmospheric carbon, such a fuel could be central to future low-carbon circular economies. Liquid biofuels, produced via industrial microbial fermentation, have similar characteristics to their petroleum counterparts with a much smaller carbon footprint.